2003
DOI: 10.1046/j.1540-8167.2003.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Para‐Hisian Entrainment: A Novel Pacing Maneuver to Differentiate Orthodromic Atrioventricular Reentrant Tachycardia from Atrioventricular Nodal Reentrant Tachycardia

Abstract: Para-Hisian entrainment/resetting can determine the course of retrograde conduction operative during narrow complex tachycardias. It is a useful diagnostic maneuver in differentiating AVNRT and orthodromic AVRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Para-Hisian pacing and entrainment were performed selectively to confirm diagnoses. 8,9 Radiofrequency ablation was performed in all patients by targeting either the SP or the AP after activation mapping or SP using the standard approach during sinus rhythm. 10 …”
Section: Methodsmentioning
confidence: 99%
“…Para-Hisian pacing and entrainment were performed selectively to confirm diagnoses. 8,9 Radiofrequency ablation was performed in all patients by targeting either the SP or the AP after activation mapping or SP using the standard approach during sinus rhythm. 10 …”
Section: Methodsmentioning
confidence: 99%
“…39 Parahisian entrainment that considered the difference in stimulus to earliest retrograde atrial activation during His and both RV and His capture has also been reported. 40 Assessment of the SA-VA and PPI-TCL intervals by parahisian entrainment may assist in differentiation between slow-fast AVNRT and AVRT, but the cutoff values are lower than that obtained with RV apical pacing (75 and 100 ms, respectively), presumably owing to conduction through the septum. 41 These techniques are rather cumbersome, requiring differential capture and both recording and identification of retrograde His and local ventricular potentials.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
“…Usually, a combined anatomical and mapping approach is employed with ablation lesions delivered at the inferior or mid part of the triangle of Koch. 60,61 Multicomponent atrial electrograms or low amplitude potentials, although not specific for identification of slow pathway -SA-VA and cPPI-TCL intervals [44][45][46][47] -Differential entrainment or cessation 48 Cumbersome Delta HA during V Pre-excitation index 49 Differential entrainment 58 pacing and tachycardia 36 Entrainment VHA pattern 37 -Anterograde His capture 50 Para-Hisian pacing 38 -Progressive fusion during or after the transition zone 51,52 Induction of retrograde Delta HA during entrainment RBBB 39 and tachycardia 53 SA init -VA and cPPI init --Para-Hisian entrainment [54][55][56] TCL conduction, are successfully used to guide ablation at these areas.…”
Section: Ablationmentioning
confidence: 99%